Susceptibility to COVID-19 Scams: The Roles of Age, Individual Difference Measures, and Scam-Related Perceptions - Nolte, Julia; Hanoch, Yaniv; Wood, Stacey; Hengerer, David (Frontiers in Psychology, 2021)
As the COVID-19 pandemic was unfolding, a surge in scams was registered across the globe. While COVID-19 poses higher health risks for older adults, it is unknown whether older adults are also facing higher financial risks as a result of COVID-19 scams. Here, we examined age differences in vulnerability to COVID-19 scams and individual difference measures (such as impulsivity, ad skepticism, and past experiences with fraud) that might help explain them. A lifespan sample (M = 48.03, SD = 18.56) of sixty-eight younger (18 – 40 years, M = 25.67, SD = 5.93), 79 middle-aged (41 – 64 years, M = 49.86, SD = 7.20), and 63 older adults (65 – 84 years, M = 69.87, SD = 4.50) recruited through Prolific completed questions and questionnaires online. In a within-subjects design, each participant responded to five COVID-19 solicitations, psychological measures, and demographic questions. Age group comparisons revealed that older adults were marginally less likely to perceive COVID-19 solicitations as genuine than middle-aged adults were. In addition, older adults perceived significantly fewer benefits than both younger and middle-aged adults did and perceived marginally higher risks than younger adults did. Hence, older adults did not exhibit greater vulnerability to COVID-19 scams. Regardless of age, intentions to respond to COVID-19 solicitations were positively predicted by higher levels of educational attainment, being married, past fraud victimization, and higher levels of positive urgency. As expected, stronger genuineness and benefit perceptions positively predicted action intentions, whereas stronger risk perceptions negatively predicted action intentions As such, COVID-19 scam susceptibility appears to be the result of a impulse control issue that is not easily inhibited, not even by past experiences of scam victimization.